Dynamics of Physico-Chemical Values in Sohshang (Elaegnus latifolia L.) across Maturity - LAMARE, R. L.; DEKA, BIDYUT C.; NATH, A.; PATEL, R. K. (Indian Journal of Hill Farming, 2014)
Sohshang (Elaegnus latifolia L.) is a large evergreen spreading type woody shrub mostly grown in semi-wild condition in the backyard garden throughout Northeast India. It is harvested during February- April when most of the major fruits are not available in the market. However, a bulk quantity of the fruit gets damaged during the process of handling and marketing due to harvesting of fruits at improper stage. Therefore, standardization of harvest maturity is required to reduce post harvest loss. Dynamics of physico-chemical values like fruit colour, pulp: seed ratio, moisture content, specific gravity, fibre, texture, total soluble sugar (TSS), ascorbic acid, total carotenoids, ÃŸ-carotene, tannins, etc. were analyzed at different stages of maturity to determine the harvest maturity of Sohshang. The present study indicated that the right stage of fruit harvesting is 75-80 days after fruit setting when the fruits develop deep orange colour and attain optimum fruit weight (11.55-61 g), TSS (>11.0 0Brix) and TSS: Acidity ratio (>3). Moreover, the fruits harvested at this stage had all the desirable qualities with a better shelf life.